If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2(x + -8) = x + 6 Reorder the terms: 5x + -2(-8 + x) = x + 6 5x + (-8 * -2 + x * -2) = x + 6 5x + (16 + -2x) = x + 6 Reorder the terms: 16 + 5x + -2x = x + 6 Combine like terms: 5x + -2x = 3x 16 + 3x = x + 6 Reorder the terms: 16 + 3x = 6 + x Solving 16 + 3x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 16 + 3x + -1x = 6 + x + -1x Combine like terms: 3x + -1x = 2x 16 + 2x = 6 + x + -1x Combine like terms: x + -1x = 0 16 + 2x = 6 + 0 16 + 2x = 6 Add '-16' to each side of the equation. 16 + -16 + 2x = 6 + -16 Combine like terms: 16 + -16 = 0 0 + 2x = 6 + -16 2x = 6 + -16 Combine like terms: 6 + -16 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| 3x-4=2(x-6)+x | | 2(1-4x)-3=4(5-2x)-3 | | 7x-2=9x+3 | | 191/4*3 | | 4x=2y+14 | | (450/18+5)/2 | | -23-(-15)= | | 3(x-1)+4x=12 | | 6a^2+29a-42= | | 1250+x(10)=2500 | | x-1-3x-3=0 | | -4-7(-5)=31 | | 7n-1(3n+4)=-2(2n-1)+10 | | 2x-5=-1+5x+2 | | 5-2(x+5)=31 | | 8(4p+1)=33p+8 | | x+5=5- | | 3/4(6+2x) | | 12-2/3m+4-3/4 | | 6-2(3r+3)=-8-7(r-3) | | .25(b+5)=-1.5 | | N/12=45/18 | | (15-7x)(-2)=30-14x | | q+37=-110 | | 7/3*9/28 | | 200m-75+62075=65975-200m | | 2d+9.7=-d-17 | | 1/6(10x-6)=8 | | 3x-y-2z=11 | | 7ya=2xb | | 3/10x+4=19 | | X+6-x-8=30 |